A Calculation Method of DC Current Reference Value for Suppressing Commutation Failure in LCC-HVDC System. Issue 1 (1st July 2022) - Chen, Xiaolong; Qi, Xiaoqing; Li, Yongli; Li, Bin; Li, Botong
Abstract: Line commutated converter based high voltage direct current (LCC-HVDC) transmission system is prone to suffer commutation failure, which can lead to the increase of DC current and the interruption of DC transmission power. Furthermore, the increase of DC current might lead to subsequent commutation failure. Based on the reactive power balance of the inverter AC bus, this paper studies the functional relationship between DC current and commutation voltage. The DC current reference value is obtained by using the DC current acquired from the above functional relationship, and combining with the DC current order given by voltage dependent current order limiter (VDCOL). This calculation method can adjust the DC current reference value in time according to the commutation voltage, thus limiting the increase of DC current. In order to verify the commutation failure suppression ability of the proposed method, several simulations are conducted based on CIGRE benchmark HVDC model in PSCAD/EMTDC. Simulation results show that the proposed method can not only suppress commutation failure successfully, but also improve the fault recovery performance of the LCC-HVDC system.